Comunidade e identidade quilombola: o Teatro do Oprimido como abordagem metodológica na escola Antônia do Socorro Silva Machado - Omar, Amanda Caline da Silva (2018)
This work, acarried out in the context Professional Master’s Degree Program in arts (PROFARTES / UFPB), presents the pedagogical research on the quilombolas identities of students of a formal and primary school, using games and exercises of the Theater of the Oppressed. The Municipal School Antônia do Socorro Silva Machado is located in south of the city of João Pessoa (PB) and was built in the urban quilombo area of Paratibe. A wide range of studies were carried out with students from the 1st year of elementary school, under the influence of theories that discuss the identity in various aspects, especially those related to black and quilombola identity. The objective is to perceive a possible identity of the students in this context, from the games applied during the drama classes. In addition, we aim to: evaluate the Theater of the Oppressed as a methodological approach for teaching theater in quilombola reality; develop activities with Theater of the Oppressed for the debate on cultural identities; as well as elaborate reflections on the developments with the practices of Theater Pedagogy in the perception and possible constitution of the quilombola identity in the school. Thus, our practices in the classroom applied games and exercises of the Theater of the Oppressed. With the use of procedures of participant observation, in the scientific method. Therefore, in order to understand the aspects that guide the process of identity formation of the group of students investigated, semi-structured interviews and conversation wheels were carried out, allowing the observation of oral discourse, body expressions and graphic design. The study was based on the behavior, interviews and participation of students in exercises applied in the theater workshop, which allowed the perception and analysis of identity aspects in the written, oral and corporal production of individuals.